Penerapan Model Pembelajaran Kooperatif Tipe Make A Match Menggunakan Kartu Berpasangan Untuk Meningkatkan Kosakata Bahasa Jepang di XI Perkantoran SMK Negeri 1 Magetan - Wulandari, Wulandari; Yeni, Yeni; Restu Handayani, Irvina (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2025)
This study aims to (1) improve mastery of Japanese vocabulary (2) determine students' responses to the implementation of cooperative learning make a match use paired cards. The research subjects were 36 class XI students. This type of research is Classroom Action Research (PTK). The data collection methods used were test methods, observation methods, and questionnaires which were then analyzed using quantitative descriptive methods. The research results show that (1) Students' mastery of Japanese vocabulary increases through the application of the cooperative type learning model make a match use paired cards. Based on the results pre-test shows the average score obtained is 52.55 with a completion percentage of 5.55%. After implementing cycle I, the average score obtained by students increased to 72.22 with a completion percentage of 58.33%. Then after implementing cycle II, the average score obtained by students increased to 80.33 with a completion percentage of 91.66%. (2) Student responses to the application of the cooperative learning model make a match in cycle I was classified as positive with an average of 29.22. Meanwhile, cycle II was also classified as positive with an average score of 30.94.